Pudrición del Cogollo and the (post-)neoliberal ecological fix in Ecuador's palm oil industry. Issue 80 (March 2017) - Johnson, Adrienne
Abstract: This paper examines the variegated natures of (post-)neoliberal environmental governance in Latin America using environmental crisis as an entry point. It examines the institutional measures put forth by Ecuador's government, in concert with other actors, to contain and manage the damaging effects of an insidious palm oil plant disease known as Pudrición del Cogollo (PC). Using empirical data collected through qualitative means, my analysis demonstrates that nature's biophysical processes – in particular, disease ecologies – can play a crucial role in the pursuit and achievement of national accumulation goals. Specifically, I argue that the ecologies of the PC crisis have been rendered functional to the Ecuadorian government's current political and economic strategies of intensified accumulation and market competitiveness. By making environmental crisis the basis of key accumulation strategies, the state is able to convert negative environmental outcomes into opportunities for profit-generation. Utilizing the notion of the 'ecological fix', this paper reveals two major conclusions: (1) plant health emergencies and the actions used to mitigate environmental crises are not only challenges but opportunities that can be mobilized to support further accumulation strategies and (2) the study of PC and Ecuador's palm oil industry provides new fruitful terrain to examine the connections between the deepening variegated effects of neoliberalism through nature and environmental crisis solutions in Latin America.